Protein Kinase C β Inhibitor LY333531 Attenuates Intercellular Adhesion Molecule-1 and Monocyte Chemotactic Protein-1 Expression in the Kidney in Diabetic Rats - Wu Yonggui; Wu Guozhong; Qi Xiangming; Lin Hui; Qian Hao; Shen Jijia; Lin Shantan (Elsevier, 2006)
Abstract.: In vitro studies have shown that activation of protein kinase C (PKC) is a key mediator of intercellular adhesion molecule-1 (ICAM-1) and monocyte chemoattractant protein-1 (MCP-1) in a range of cell types and in response to high glucose, however, its role in the in vivo setting has not been clearly delineated. Streptozotocin-induced diabetic rats were treated with the PKC-β isoform inhibitor LY333531 for 8 weeks. LY333531 treatment significantly attenuated increased urinary albumin excretion rate and glomerular volume and tubulointerstitial injury index as well as elevated PKC activity and PKC-β protein expression in the kidney. Level of malondialdehyde was markedly higher and antioxidant enzyme activity such as superoxide diamutase and catalase as well as glutathione peroxidase were significantly lower in the kidney from diabetic rats than that of the control group. LY333531 administration could remit these changes. Increased macrophages recruitment as well as ICAM-1 and MCP-1 protein expression in the kidney were significantly inhibited by LY333531 in diabetic rats. It is concluded that mechanism of renoprotection of LY333531 may be correlated, at least partly, with suppression of increased macrophages recruitment and overexpression of ICAM-1 and MCP-1 in diabetic rats. Keywords:: LY333531, diabetes mellitus, macrophage, intercellular adhesion molecule-1, monocyte chemotactic protein-1